EKSISTENSI PERUSAHAAN DALAM PELAKSANAAN FUNGSI DAN TUJUANNYA DI MASYARAKAT - Derita Prapti Rahayu (Faculty of Law, Universitas Diponegoro, 2010)
Existence of Company is Existence of based Company activitys of economics expanding to go forwardsociety through some function and target him where conducted by body or individualness of effort both forlegal company and a/so do not conducted the lega/ company continually by creating service and goods tomarketing and also obtain, get advantage. Company classification is classification of is each company ofgoodness of effort based private sector efforl and a/so state to the founding, arrangement and alsoresponsibility as according to applicable law order.